Kaum Muda dan Industri Kreatif Kriya Tenun “Songke” Manggarai-Flores, NTT - Haryatno, Yulius Rudi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Since Labuan Bajo, West Manggarai, NTT was designated as one of the super priority destinations in 2019, there have been many creative industries that have also developed there. One of the developing creative industries is songke woven fabric. The creative industry in the craft sector is considered to have a positive influence on the employment sector, economic welfare and business. Ironically, even though it has the potential to contribute to (economic) welfare, the creativity of weaving is still loved by artisans of a certain age group (35-60 years old). Productive young people (generation Y) seem less interested in this weaving creativity. Therefore, this study aims to explore qualitatively-analystically the reasons the lack of interest of young people in the creative weaving industry. The results of this analytical research indicate that traditional production patterns, informal work patterns, and a strong patriarchal culture are the basis for Manggarai youth not to get involved in the creative weaving industry.